Consuming the past into the present: The case of the Iberians (Valencia, Spain). Issue 1 (11th February 2021) - Santamarina, Beatriz; Vizcaíno, Tono
Abstract: In this article, we aim to focus on how the Iberian past (sixth century to the first century BC) has been used both to shape identities and to produce values in the marketplace and how the triad of the past, authenticity, and tradition is key in the commodification of the Iberian world. To do so, we will examine developments in the village of Moixent (Valencia, Spain). In this town, the Iberians and their archaeological remains are presented as the protagonists of the area, accompanied by several "heritage stratifications." Through case studies of family-run wineries, we analyze the process of symbolic appropriation of the Iberians in the local wine sector and its confluence with cultural tourism as well as how it has led to the development of territorial branding based on the past.